A Concept of a Production Flow Control System Protocol to exchange Data and block defective discrete Products - Jaroslaw CHROBOT (Communications of International Proceedings, 2025)
Simple data registration is often insufficient on its own, making the implementation of systems that enhance traceability with error-prevention and blocking features a crucial addition. Scientific literature typically focuses on product or process traceability limited to data collection and analysis, primarily through reporting. In contrast, the core innovation of the proposed Production Flow Control (PFC) protocol lies in its ability to automatically block defective products at the source of the issue by analyzing database content in real time. The development process began with the design of the PLC data block structure, followed by the creation of procedures on both the PLC and PFC sides. In addition, a communication algorithm between the PFC system and the PC controlling the production station was designed. A corresponding database structure, including functions and triggers, was also developed to align with the PFC communication protocol. This paper advances the understanding of Product Flow Control (PFC) systems by examining the underlying principles and functional concepts involved in their implementation. The proposed methodology is specifically designed for discrete manufacturing processes that handle distinct mechanical products. In the author's view, both scientific literature and commercial solutions tend to focus primarily on traceability - limited to data collection and registration - supplemented by reporting tools for reactive quality management. However, this may not be sufficient. As a result, the integration of a poka-yoke mechanism, such as a PFC system, is often essential to ensure proactive error prevention and enhanced process reliability.
Keywords: traceability; flow control; blocking of defected products